Seasonal Variation in Skin Cancer Diagnosis - Bianconi, Fortunato; Masanotti, Giuseppe M.; Liso, Arcangelo; La Rosa, Francesco; Duca, Emilio; Stracci, Fabrizio (Frontiers in Public Health, 2016)
Purpose. Seasonality of skin cancer is well known and it is influenced by a number of variables such exposure and personal characteristics but also health service factors. We investigated the variations in the diagnosis melanoma skin cancer (MSC) and non-melanoma skin cancer (NMSC) during the year. Methods. We analyzed incident cases recorded in the Umbria Regional Cancer registry from 1994 to 2010 (1,745 cases of MSC, 50% females and 15,992 NMSC, 41% females). The Walter-Elwood test was used to as-sess seasonal effects. Relative risks were analyzed using negative binomial regression and splines. Results. Seasonality of MSC and NMSC was similar. Incidence peaks were observed in weeks 8, 24 and 43 (Feb-ruary, July and October) and troughs in weeks 16, 32, 1 and 52 (August and December). Both NMSC and MSC cancers showed most elevated risks in autumn. A seasonal effect was present for trunk (p<0.001) and absent for face cancers (p=0.3). Conclusions. The observed pattern of diagnoses presumably depends on health service factors (e.g., organiza-tion of melanoma days, reduced access to care in August and during Christmas holidays) and personal factors (e.g., unclothing in the summer, delays in seeking care). High incidence rates in autumn could also in part de-pend on a late cancer progression effect of UV exposure. More efforts should be placed in order to guarantee uniform access to care through the year.